Ultra-low dose immunoPET using 64Cu-rituximab tracer for a human CD20 mouse model - Habte, Frezghi; Natarajan, Arutselvan (Frontiers in Medicine, 2025)
Antibodies (Abs) and their fragments can be labeled with PET radioisotope (immunoPET) for in vivo diagnostic imaging. Compared to the conventional FDG-PET, immunoPET can be designed to target in vivo cancer-specific antigen expression levels for various tumors and metastasis, which makes immunoPET (iPET) a powerful technique for molecular imaging and therapy monitoring. However, achieving the optimal dose to minimize radioisotope toxicity without compromising the visualization of the smallest tumor is challenging. To find an ultra-minimal tracer dose, we have developed a novel iPET with an intact rituximab Ab labeled with 64Cu to image human CD20 (hCD20) in a transgenic mouse model for non-Hodgkin’s lymphoma (NHL) imaging. Using phantom and in vivo mouse models, we optimized the minimal dose that can be administered in a mouse using a high-specific iPET tracer prepared from 64Cu-rituximab. A phantom study was used to characterize the scanner capability and limit for imaging using low doses. An ultra-minimal dose administered in a mouse model showed good image quality with high signal-to-noise ratio without compromising quantitative accuracy. The phantom study with below 50 μCi dose level indicated a slight increase in variability due to reduced dose specifically for target regions with lower uptakes (<3:1 ratio) relative to the background. In vivo study performed with four groups of mice (n = 3), each group injected with ~90, ~50, ~25, and ~10 μCi showed a linear increase of tracer uptake measured as percentage injected dose per gram (%ID/g). This tracer has shown high specific uptake in the spleen, where most B-cells are engineered to express hCD20. The study demonstrated that the lowest dose threshold limit for 64Cu-antibody-based iPET was about 25 μCi while achieving a high-quality image and quantitative accuracy.